1991
DOI: 10.1002/ppul.1950110112
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast computerized tomography of the chest in cystic fibrosis: A new scoring system

Abstract: Assessing the presence and severity of bronchiectasis (BR) and mucoid impaction (MI) of the airways in cystic fibrosis (CF) is difficult by non-invasive methods. We hypothesized that scoring ultrafast computerized tomograms (UFCT) of the chest for BR and MI could be useful in detecting early lung changes in 28 patients with CF. To do this, UFCT scores were compared to established clinical and chest X-ray (CXR) scores. Results showed that UFCT scores correlated highly with clinical (r = 0.88) and CXR (r = 0.93)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 8 publications
1
69
0
1
Order By: Relevance
“…In several studies in which the relationship between lung structure and function has been measured, a strong correlation between measures of forced expiratory flow and HRCT scoring systems has been reported [37,99,138,146,147], except in studies of very young children [128,134,143]. The results of two longitudinal studies have suggested that HRCT scoring may be more sensitive than lung function in detecting disease progression in CF; in both studies, pulmonary function tests (PFTs) remained stable over 2 yrs, whereas the HRCT score detected worsening of disease [36,130].…”
Section: Airway Imaging In Cystic Fibrosismentioning
confidence: 99%
“…In several studies in which the relationship between lung structure and function has been measured, a strong correlation between measures of forced expiratory flow and HRCT scoring systems has been reported [37,99,138,146,147], except in studies of very young children [128,134,143]. The results of two longitudinal studies have suggested that HRCT scoring may be more sensitive than lung function in detecting disease progression in CF; in both studies, pulmonary function tests (PFTs) remained stable over 2 yrs, whereas the HRCT score detected worsening of disease [36,130].…”
Section: Airway Imaging In Cystic Fibrosismentioning
confidence: 99%
“…In numerous studies, expert reader CT scan scores have been shown to correlate with other CF lung disease parameters, including clinical status and lung function. [10][11][12][13][14][15][16][17] Although expert visual scoring such as the Brody scoring system 16 includes more features of CF lung disease than can be evaluated by automated software, it is time consuming and limited by the number of expert readers available. In contrast, automated computer analysis does not require specially trained observers, avoids observer bias and variability, offers better standardization, and function measures, and sputum markers of infl ammation in children with CF.…”
mentioning
confidence: 99%
“…This tomosynthesis scoring system is based on previously reported scoring systems for radiography [3][4][5][6][7][8][9][10][11][12][13] and CT [14][15][16][17][18][19][20][21][22]. Typical findings of CF pulmonary disease seen with tomosynthesis and evaluated with the scoring system are overinflation, bronchial wall thickening, parenchymal lesions, bronchiectasis and mucus plugging.…”
Section: Discussionmentioning
confidence: 99%
“…In tomosynthesis this method is not optimal as the vessels in the periphery of the lungs are often difficult to define in patients with severe CF changes, which would make measurements unreliable. In the CT scoring system of Nathanson [15], on the other hand, bronchi affected by bronchiectasis are scored for appearance (cylindrical, saccular or cystic) and for extent. In the proposed tomosynthesis scoring system bronchiectatic bronchi are rated for number and appearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation